Teologi Islam Perspektif Fazlur Rahman - Haerul Anwar (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2014)
This writing will analyze views belonging to Fazlur Rahman in theological issues from different angle. In majority, theological discourses developed by the ancient theologists were concentrated into matters of god and godhood, and this results theological discourses becoming verily theocentrist. As the result, this creates formulas and arguments which are complicated and cannot be perceived by common people. For that, Fazlur Rahman reconstructed the previous theological concepts by relating to Islamic theological basics and practical values in life, and he also advanced moral aspect belonging to human race; so theology is no longer theocentrist but anthropocentrist. Through this Rahman’s effort, theology then becomes more relevant with nowadays context and is easily understood by common people. In this context, Rahman analyzes three main theological questions: revelation and prophethood, free will and predestination, and escathology.